2021
DOI: 10.1097/spv.0000000000000830
|View full text |Cite
|
Sign up to set email alerts
|

Are White Matter Tract Integrities Different in Multiple Sclerosis Women With Voiding Dysfunction?

Abstract: Objectives Two white matter tracts (WMTs) are proposed to be involved in bladder function: anterior thalamic radiation and superior longitudinal fasciculus. Multiple sclerosis (MS) patients with voiding dysfunction (VD) may have distinct changes in these 2 WMTs. This study aims to compare the fractional anisotropy (FA) and mean diffusivity (MD) from diffusion tensor imaging of MS females with and without VD versus healthy controls (HCs). Methods Prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Due to the demyelinating nature of MS, alternation of grey and white brain matters characteristics and connectivity might present differently in patients who have VD and those who do not. Previous studies have shown differences in both grey and white brain matter in MS patients with NLUTD who have VD compared with those who do not 8,20–22 . In this study, we demonstrate the ability of using ML to both classify and predict development of VD in MS patients using their neuroimaging information.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Due to the demyelinating nature of MS, alternation of grey and white brain matters characteristics and connectivity might present differently in patients who have VD and those who do not. Previous studies have shown differences in both grey and white brain matter in MS patients with NLUTD who have VD compared with those who do not 8,20–22 . In this study, we demonstrate the ability of using ML to both classify and predict development of VD in MS patients using their neuroimaging information.…”
Section: Discussionmentioning
confidence: 59%
“…VD compared with those who do not. 8,[20][21][22] In this study, we demonstrate the ability of using ML to both classify and predict development of VD in MS patients using their neuroimaging information. In grey matter areas, all MS individuals showed strong connectivity in the frontal brain regions while cerebellar regions exhibited reduced connectivity.…”
Section: Sc As Predictorsmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, the superior longitudinal fasciculus (SLF) was also found to have 8% of the global white matter hyperintensity (WMH) burden and connect to regions activated during bladder filling 10 . Similarly, Tran et al 12 found a lower mean FA and higher mean MD in both the ATR and SLF in MS patients with voiding dysfunction when compared to MS patients without voiding dysfunction.…”
Section: Methodsmentioning
confidence: 95%
“…[9,10] Dynamic imaging studies, such as positron emission tomography-computed tomography (PET-CT) and functional magnetic resonance imaging (fMRI) modalities, have been implemented to better characterize this complex disease process. [11][12][13] Previously, our team found distinct functional connectivity (FC) patterns using fMRI [13] with more damage in the left anterior thalamic radiation (ATR) on diffusion tensor imaging (DTI) [14] in patients with VD compared to those without. In this study, we aim to assess the grey and white matter of female MS patients with DSD, specifically the FC of brain regions that are activated at the initiation of voiding, and the integrity of two white matter tracts; the ATR and the superior longitudinal fasciculus (SLF), via their fractional anisotropy (FA) and mean diffusivity (MD) values.…”
Section: Introductionmentioning
confidence: 99%